Stain-resistant, anti-slip and wear-resistant anti-slip corundum dry granular glaze, ceramic tile and process and application of ceramic tile
By using high-melting point matte dry particles and high-temperature melted corundum powder and antique protective glaze in ceramic products, a composite structural surface is formed, which solves the problems of unstable anti-slip and insufficient stain resistance of existing ceramic products, and achieves high-level anti-slip, stain resistance and easy cleaning.
Patent Information
- Application Number
- CN202411781879.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-07
AI Technical Summary
The surface of existing anti-slip tiles is rough after being fired at high temperature, which is prone to concealing dirt and unstable anti-slip performance. The anti-slip properties decrease after long-term use, affecting public safety.
Matt dry particles with an initial melting temperature of 1200℃ or above and corundum powder with a melting temperature of 2000℃ or above combined with antique protective glaze to form a rough composite structural surface of micron and nano-level. The surface of ceramic products is anti-slipped to R11 or above, and it is characterized by hydrophobic and easy to clean.
It realizes high-level anti-slip performance, stain resistance and easy cleaning of the surface of ceramic products, and improves the wear resistance of the product, solving the problem that existing ceramic surfaces cannot have both stain resistance, anti-slip and Mohs hardness.
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic tiles, in particular to anti-fouling, anti-skid, and wear-resistant anti-skid corundum dry granule glaze and ceramic tiles, and a process and application thereof. Background Art
[0002] The existing anti-slip tile preparation process requires the use of dry granular materials with coarse particles and high temperature so that the anti-slip level of the prepared glaze meets the requirements. The main thing is to retain the rough surface after high-temperature firing in the kiln. The product's anti-slip level reaches R11 or above to have a significant anti-slip effect. However, there are often some tiny gaps between the dry particles with rough surfaces, which can easily lead to surface conditions such as dust accumulation, dirt accumulation, and difficulty in cleaning; at the same time, if the dry particle temperature is reduced and ultra-fine dry particles are used, the anti-slip performance index of the brick surface will decrease, and the anti-slip level cannot be stabilized above R11; further, anti-slip tiles are generally used in outdoor public places with large traffic, which means that the soles of shoes and the sand on the soles of shoes rub against the surface of the anti-slip tiles for a long time, causing the raised anti-slip dry particles on the surface of the anti-slip tiles to be easily worn, resulting in a decrease in anti-slip performance after long-term use, affecting public safety. Summary of the invention
[0003] The purpose of the present invention is to provide an anti-slip corundum dry particle glaze, which selects matte dry particles with an initial melting temperature of more than 1200°C and corundum powder melted at more than 2000°C for application in antique protective glazes. The glaze can form a rough composite structure surface at the micron level and nanometer level under the composite action. The surface anti-slip of the ceramic product reaches R11 or above, and the surface is also hydrophobic and easy to clean.
[0004] The present invention also provides a glazing process for a dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze, which can exert the best performance of the anti-skid corundum dry granular glaze when sprayed according to specific construction parameters.
[0005] The present invention also provides a stain-resistant, skid-resistant, and wear-resistant ceramic tile, which uses the above-mentioned anti-skid corundum dry granular glaze to form a wear-resistant and skid-resistant layer, and is combined with a hydrophobic and stain-resistant coating.
[0006] The invention also proposes the use of anti-skid corundum dry granular glaze in preparing anti-fouling, anti-skid and wear-resistant ceramic tiles.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] A dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granule glaze, comprising, by mass percentage: 10-50% of antique protective glaze, 5-40% of matte dry granules, and 10-50% of corundum powder, and an additional suspending agent of 1-5 times the total mass of the corundum powder;
[0009] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2-1.5%, and the content of BaO plus MgO is greater than 20%;
[0010] The matte dry particles have a particle size of 120 to 300 meshes and a melting point greater than 1200°C;
[0011] The particle size of the corundum powder is 200-1200 meshes.
[0012] Optimally, the antique protective glaze comprises, by mass, 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 6 to 10 parts of kaolin, 2 to 8 parts of zinc oxide, 3 to 10 parts of burned talc, 5 to 15 parts of wollastonite, 15 to 25 parts of barium carbonate and 2 to 8 parts of strontium carbonate.
[0013] The chemical composition of the matte dry granules, by mass percentage, includes: SiO 2 45~65%、Al 2 O 3 6~15%、K 2 O 3~10%、Na 2 O 0~2.5%, CaO 6~15%, MgO 0~1%, BaO 0~2% and ZnO 3~12%.
[0014] A glazing process for a dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze, using the dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze, and applying the anti-skid corundum dry granular glaze by spraying;
[0015] The construction parameters of the anti-slip corundum dry granular glaze are: specific gravity 1.2-1.6 g / cm 3 The glaze spraying amount is 100-250g / m2, and the nozzle aperture is 0.43-0.72mm.
[0016] A stain-resistant, skid-resistant and wear-resistant ceramic tile, comprising: a body, a wear-resistant and skid-resistant layer and a hydrophobic and stain-resistant coating;
[0017] The wear-resistant and anti-skid layer is the above-mentioned anti-fouling, anti-skid, and anti-wear anti-skid corundum dry granular glaze;
[0018] The wear-resistant and anti-skid layer is arranged on the surface of the blank; the hydrophobic and anti-fouling coating is applied on the surface of the wear-resistant and anti-skid layer; the hydrophobic and anti-fouling coating is prepared and cured by the hydrophobic and anti-fouling coating.
[0019] Optimally, the hydrophobic and anti-fouling coating comprises: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, a silane coupling agent and a curing agent.
[0020] Optimally, the curing agent includes: epoxy acrylate resin.
[0021] Optimally, the size of the nano-silicon dioxide is in the range of 10 to 50 nm.
[0022] A preparation process of a stain-resistant, non-slip and wear-resistant ceramic tile comprises the following steps:
[0023] (1) Using the above-mentioned anti-fouling, anti-skid, and wear-resistant anti-skid corundum dry granular glaze glazing process, the anti-skid corundum dry granular glaze is applied to the brick blank, and placed in a kiln for firing at 1200-1300° C.;
[0024] (2) The bricks are taken out of the kiln, cooled to 100-250°C, and sprayed with a hydrophobic and anti-fouling coating, and the residual heat of the bricks is used to cure the hydrophobic and anti-fouling coating;
[0025] The hydrophobic and anti-fouling coating includes: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, silane coupling agent and curing agent.
[0026] Optionally, the method further comprises: step (3);
[0027] Step (3): transferring the bricks to an ultraviolet environment to continue curing;
[0028] In the step (2), the curing agent includes: epoxy acrylate resin.
[0029] A use of an anti-skid corundum dry granular glaze in preparing stain-resistant, anti-skid, and wear-resistant ceramic tiles. The anti-skid corundum dry granular glaze is the above-mentioned anti-skid, anti-skid, and wear-resistant anti-skid corundum dry granular glaze.
[0030] Compared with the prior art, one of the above technical solutions has the following beneficial effects:
[0031] The present invention provides a non-slip corundum dry particle glaze, which selects matte dry particles with an initial melting temperature of more than 1200°C and corundum powder melted at more than 2000°C for application in antique protective glazes. Under the combined action, a rough composite structure surface at the micron level and nanometer level can be formed. The surface anti-slip performance of the ceramic product reaches R11 or above, and the surface is also hydrophobic and easy to clean, which solves the problem that the existing ceramic surface cannot have the advantages of stain resistance, anti-slip performance and Mohs hardness at the same time. DETAILED DESCRIPTION
[0032] For ease of understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the documents in this area or the product instructions are carried out. The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be obtained by commercial purchase.
[0033] A dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granule glaze, comprising, by mass percentage: 10-50% of antique protective glaze, 5-40% of matte dry granules, and 10-50% of corundum powder, and an additional suspending agent of 1-5 times the total mass of the corundum powder;
[0034] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2-1.5%, and the content of BaO plus MgO is greater than 20%;
[0035] The matte dry particles have a particle size of 120 to 300 meshes and a melting point greater than 1200°C;
[0036] The particle size of the corundum powder is 200-1200 meshes.
[0037] The present invention provides a non-slip corundum dry particle glaze, which selects matte dry particles with an initial melting temperature of more than 1200°C and corundum powder melted at more than 2000°C for application in antique protective glazes. Under the combined action, a rough composite structure surface at the micron level and nanometer level can be formed. The surface anti-slip performance of the ceramic product reaches R11 or above, and the surface is also hydrophobic and easy to clean, which solves the problem that the existing ceramic surface cannot have the advantages of stain resistance, anti-slip performance and Mohs hardness at the same time.
[0038] Specifically, the antique protective glaze of the present scheme can be replaced by the known antique protective glaze, which can be purchased directly from the market. Generally, the antique protective glaze is based on the crystallization produced by the high barium formula or the high magnesium formula, while the present scheme requires the antique protective glaze to require the content of BaO plus MgO to be greater than 20%, and the known antique protective glaze can be fired at a temperature greater than 1200°C in the kiln. As the main component glaze is very suitable as a carrier of matte dry particles, corundum powder, etc. As the water content of the glaze evaporates, the large and small particles in the liquid phase begin to expose the surface; among them, the matte dry particles with a particle size of 120 to 300 meshes and the corundum powder with a particle size of 200 to 1200 meshes form a secondary layout on these most basic three-dimensional basic structures, forming a three-dimensional structure with a roughness of 10 to 125 microns; and the main component of the finest particles on the surface with a particle size of 10 to 75 microns is corundum particles. Since both dry particles and corundum are high temperature resistant raw materials, the basic surface morphology before firing can be maintained after kiln firing, that is, the basic undulating surface with a roughness size in the micrometer and millimeter range, and this undulating surface can lay the foundation for the subsequent anti-slip to reach R11 or above, and also prepare a good implantation for the subsequent preparation of the nano-hydrophobic layer. Among them, the suspending agent is a conventional component in ceramic glazes, which can be purchased directly from the market at random, and can be selected into different types according to needs. It is generally composed of water-soluble polymer high viscosity materials or bentonite, etc. The amount of suspending agent added is generally adjusted according to the amount of matte dry particles and corundum powder added. The more corundum powder, the more suspending agent is added, ensuring that the matte dry particles and corundum powder will not precipitate during glazing.
[0039] Optimally, the antique protective glaze comprises, by mass, 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 6 to 10 parts of kaolin, 2 to 8 parts of zinc oxide, 3 to 10 parts of burned talc, 5 to 15 parts of wollastonite, 15 to 25 parts of barium carbonate and 2 to 8 parts of strontium carbonate.
[0040] The antique protective glaze of this scheme can be replaced with an antique protective glaze on the market as needed. In the optimal embodiment, the antique protective glaze is composed of potassium feldspar, sodium feldspar, kaolin, zinc oxide, burned talc, wollastonite, barium carbonate and strontium carbonate, and is mixed according to the above ratio to obtain the optimal embodiment, which lays the foundation for anti-slip performance reaching R12.
[0041] Preferably, the chemical composition of the matte dry particles, by mass percentage, includes: SiO 2 45~65%、Al 2 O 3 6~15%、K 2 O 3~10%、Na 2 O 0~2.5%, CaO 6~15%, MgO 0~1%, BaO 0~2% and ZnO 3~12%.
[0042] A glazing process for a dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze, using the dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze, and applying the anti-skid corundum dry granular glaze by spraying;
[0043] The construction parameters of the anti-slip corundum dry granular glaze are: specific gravity 1.2-1.6 g / cm 3 The glaze spraying amount is 100-250g / m2, and the nozzle aperture is 0.43-0.72mm.
[0044] Based on the above-mentioned matte dry particle size of 120-300 mesh, the corundum powder particle size of 200-1200 mesh, the dry particle size raised on the surface of the glaze layer is comprehensively considered to be 10-125 microns. Combined with the spray glaze droplet size, the comprehensive anti-slip corundum dry particle glaze surface roughness is obtained: 10-500 microns. More specifically, in the optimal embodiment of this scheme, the anti-slip corundum dry particle glaze is applied by spraying, specifically, the anti-slip corundum dry particle glaze is at a specific gravity of 1.2-1.6 g / cm 3, the construction parameters of the spraying amount of glaze are 100-250g / m2 and the nozzle aperture is 0.43-0.72mm. The anti-slip corundum dry granule glaze has a high specific gravity, a small amount of glaze, a large nozzle aperture, and the brick surface has obvious dot-like undulations after spraying. The size of the atomized droplets is 0.02-0.08mm, and the size is increased to 0.10-0.50mm through multiple superpositions, forming the most basic three-dimensional basic structure, like the basic layout of the "peak". As the water in the droplets evaporates, the large and small particles in the droplets begin to appear on the surface, among which the high-temperature dry particles with a particle size of 120-300 mesh and the corundum powder with a particle size of 200-1200 mesh form a secondary layout on the basis of these three-dimensional basic structures, forming a secondary three-dimensional structure with a roughness range of 10-125 microns, which can be regarded as the arrangement of "trees and shrubs" on the "peak". After leaving the kiln, the hydrophobic and anti-fouling coating can be sprayed to instantly fill the nano coating into every gap of the base undulating surface with a roughness size in the micron and millimeter range, forming a complete film layer with a thickness of 1 to 5 microns. Because the nano coating liquid flows under its own weight, the deeper the depression, the thicker the film layer, and the more obvious the corresponding anti-fouling and hydrophobic effects.
[0045] A stain-resistant, skid-resistant and wear-resistant ceramic tile, comprising: a body, a wear-resistant and skid-resistant layer and a hydrophobic and stain-resistant coating;
[0046] The wear-resistant and anti-skid layer is a dirt-resistant, anti-skid, wear-resistant and anti-skid corundum dry granular glaze in any of the above embodiments;
[0047] The wear-resistant and anti-skid layer is arranged on the surface of the blank; the hydrophobic and anti-fouling coating is applied on the surface of the wear-resistant and anti-skid layer; the hydrophobic and anti-fouling coating is prepared and cured by the hydrophobic and anti-fouling coating.
[0048] The hydrophobic and stain-resistant coating can be replaced by a known coating with wear-resistant and stain-resistant functions, and can be directly replaced by a coating available on the market.
[0049] The hydrophobic and anti-fouling coating can be optimized to include: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, silane coupling agent and curing agent. The mass ratio of hydrogenated silicone oil: silicone resin: nano-silicon dioxide: silane coupling agent: curing agent is (1.0-2.5): (5-15): (1.0-2.0): (0.1-0.6): (5-10).
[0050] The hydrophobic and anti-fouling coating of this scheme preferably uses hydrogenated silicone oil, silicone resin and nano-silicon dioxide in combination. This is because the hydrophobic and anti-fouling coating is sprayed or applied at a temperature of 100-250°C on the brick embryo. Under the action of high temperature, the silane coupling agent first produces a cross-linking reaction and begins to solidify. For some thermally cured curing agents, they will also be further deeply solidified to ensure that the hydrophobic and anti-fouling coating film is firmly combined with the rough three-dimensional basic structure of the ceramic surface in the micron and millimeter range, and finally superimposed to form a hydrophobic surface with a roughness of micron + nanometer size. And the surface nanostructure contains the silicon hydrogen bond of hydrogenated silicone oil and nano-silicon dioxide, which creates the final appearance of the surface being hydrophobic and easy to clean.
[0051] Optimally, the curing agent includes: epoxy acrylate resin.
[0052] The curing agent of the present scheme can be cured using a thermal curing agent; and in the optimal embodiment, the present scheme preferably uses epoxy acrylate resin as the curing agent, which is mainly cross-linked and cured by silane coupling agent under high temperature, and epoxy acrylate resin is mainly photocured; under the action of environmental ultraviolet rays such as sunlight, epoxy acrylate resin can produce further deep photocuring, ensuring sufficient curing time without the need to maintain a high temperature state, thereby ensuring that the hydrophobic and stain-resistant coating film is firmly bonded to the basic undulating ceramic three-dimensional appearance in the micron and millimeter range.
[0053] Optimally, the size of the nano-silicon dioxide is in the range of 10 to 50 nm.
[0054] The size of the nano-silicon dioxide in this solution can be selected in any nano-size range as needed; and in the optimal embodiment, the size of the nano-silicon dioxide is 10-50nm, and the presence of 10-75 micron corundum particles in the wear-resistant and anti-skid layer can comprehensively improve the surface of the micron-nano rough composite three-dimensional structure, so that the surface hardness of the product reaches Mohs 7-8, which is much higher than the general coating hardness and higher than the general ceramic glaze hardness.
[0055] A preparation process of a stain-resistant, non-slip and wear-resistant ceramic tile comprises the following steps:
[0056] (1) Using a glazing process of a dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze according to any of the above embodiments, the anti-skid corundum dry granular glaze is applied to a brick blank, and the brick blank is placed in a kiln and fired at 1200-1300° C.;
[0057] Before applying the anti-slip corundum dry granular glaze, a base glaze may be applied on the brick blank in advance. The base glaze is a well-known component used to improve the bonding degree of the slippery corundum dry granular glaze to the brick blank.
[0058] (2) The bricks are taken out of the kiln, cooled to 100-250°C, and sprayed with a hydrophobic and anti-fouling coating, and the residual heat of the bricks is used to cure the hydrophobic and anti-fouling coating;
[0059] The hydrophobic and anti-fouling coating comprises: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, silane coupling agent and curing agent. The mass ratio of hydrogenated silicone oil: silicone resin: nano-silicon dioxide: silane coupling agent: curing agent is (1.0-2.5): (5-15): (1.0-2.0): (0.1-0.6): (5-10).
[0060] This scheme preferably applies hydrophobic and stain-resistant coating, because by spraying, the hydrophobic and stain-resistant coating can be instantly filled into every gap of the base undulating surface with a roughness size in the micron and millimeter range, forming a complete film layer with a thickness of 1 to 5 microns; and the coating liquid flows under the action of its own weight, the deeper the depression, the thicker the film layer, and the corresponding stain-resistant and hydrophobic effects are more obvious, so that the tiles have both stain resistance, anti-slip properties and Mohs hardness.
[0061] Optionally, the method further comprises: step (3);
[0062] Step (3): transferring the bricks to an ultraviolet environment to continue curing;
[0063] In the step (2), the curing agent includes: epoxy acrylate resin.
[0064] The hydrophobic and stain-resistant coating of the present scheme may not be completely cured during thermal curing at 100-250°C. In order to increase the curing time of the hydrophobic and stain-resistant coating, the bricks are further transferred to the ultraviolet light or ultraviolet lamp atmosphere in the sunlight environment, and the epoxy acrylate resin can be further deeply photocured to ensure sufficient curing time without maintaining a high temperature state, thereby ensuring that the hydrophobic and stain-resistant coating film is firmly bonded to the basic undulating ceramic three-dimensional appearance in the micron and millimeter range.
[0065] A use of an anti-skid corundum dry granular glaze in preparing stain-resistant, anti-skid, and wear-resistant ceramic tiles. The anti-skid corundum dry granular glaze is the above-mentioned anti-skid, anti-skid, and wear-resistant anti-skid corundum dry granular glaze.
[0066] Performance Test:
[0067] Anti-slip property: Use the "DIN51130 Anti-slip Test for Bottom Plates" to conduct an anti-slip test on the brick surface.
[0068] Stain resistance: Using the test method of GB / T3810.14-2016 "Test methods for tiles Part 14 Determination of stain resistance - Building materials standard", the green dye in light oil is used as the pollutant to test the stain resistance of the product glaze. A stain resistance level of 5 is qualified.
[0069] Mohs hardness: The brick surface is tested on Mohs hardness according to European standard EN15771:2010.
[0070] Embodiment A1:
[0071] A preparation process of a stain-resistant, non-slip and wear-resistant ceramic tile, comprising:
[0072] (1) Spray the anti-slip corundum dry granular glaze on the brick with the base glaze attached. The construction parameters are: specific gravity 1.4g / cm 3 , glaze spraying amount 200g / m2, nozzle aperture 0.6mm; fired in kiln at 1250℃; bottom glaze is purchased randomly on the market;
[0073] The anti-slip corundum dry particle glaze includes, by mass percentage: 40% of antique protective glaze, 20% of matte dry particles and 40% of corundum powder, and an additional suspending agent of 1 times the total mass of the corundum powder is added; the suspending agent is purchased randomly on the market.
[0074] The antique protective glaze is ball-milled to 1% residue on a 325-mesh sieve; the particle size of the matte dry particles is 120-300 mesh, and the initial melting temperature is 1200°C; the particle size range of the corundum powder is 200-1200.
[0075] The antique protective glaze includes, by mass, 25 parts of potassium feldspar, 20 parts of sodium feldspar, 8 parts of kaolin, 6 parts of zinc oxide, 6 parts of burned talc, 10 parts of wollastonite, 20 parts of barium carbonate and 6 parts of strontium carbonate.
[0076] The chemical composition of matte dry granules, by mass percentage, includes: SiO 2 60%、Al 2 O 3 10%, K 2 O 8%, Na 2 O2%, CaO 8%, MgO 1%, BaO 1% and ZnO 10%.
[0077] (2) The bricks are taken out of the kiln, cooled to 200°C, and sprayed with a hydrophobic and anti-fouling coating, and the residual heat of the bricks is used to cure the hydrophobic and anti-fouling coating;
[0078] The hydrophobic and anti-fouling coating includes: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, silane coupling agent and epoxy acrylate resin; the size range of nano-silicon dioxide is 30nm;
[0079] The mass ratio of hydrogenated silicone oil: silicone resin: nano-silica: silane coupling agent: epoxy acrylate resin is 2:10:1:0.5:8.
[0080] (3) Transfer the bricks to an outdoor environment and continue to cure under sunlight for 6 hours.
[0081] Embodiment A2:
[0082] The basic steps of Example A2 are the same as those of Example A1, except that the antique protective glaze of Example A2 is purchased directly from the market, and the chemical composition of the raw materials, by mass percentage, includes: SiO 2 50%, Al 2 O 3 10%, K 2 O 3%, Na 2 O 3%, CaO 6%, MgO 1%, SrO 2%, BaO 20% and ZnO 5%.
[0083] Comparative Example A1:
[0084] The basic steps of Comparative Example A1 are the same as those of Example A1, except that the anti-slip corundum dry particle glaze of Comparative Example A1 includes, by mass percentage, 50% of antique protective glaze and 50% of matte dry particles, and the amount of suspending agent added is the same as that of Example A1.
[0085] Comparative Example A2:
[0086] The basic steps of Comparative Example A2 are the same as those of Example A1, with the only difference being that the anti-slip corundum dry particle glaze of Comparative Example A2 uses ordinary dry particles instead of the matte dry particles of Example A1, and the raw materials of the ordinary dry particles, by mass percentage, include: 30% albite, 10% potassium feldspar, 15% dolomite, 10% zircon powder, 10% calcite, 5% barium carbonate, 6% fluorite and 14% quartz.
[0087] Comparative Example A3:
[0088] The basic steps of Comparative Example A3 are the same as those of Example A1, except that the anti-slip corundum dry particle glaze of Comparative Example A3 eliminates the matte dry particles, specifically, by mass percentage, including: 96% of antique protective glaze and 4% of corundum powder, and the same suspending agent as Example A1 is added.
[0089] The performance tests of Examples A1 and A2 and Comparative Examples A1 and A2 were performed, and the results are shown in Table 1 below.
[0090] Table 1 - Performance Tests of Example A
[0091] project Surface stain resistance Anti-slip Mohs hardness Example A1 qualified R12 Level 8 Example A2 qualified R11 Level 7 Comparative Example A1 Failure R9 Level 6 Comparative Example A2 Failure R9 Level 6 Comparative Example A3 Failure R9 Level 6
[0092] illustrate:
[0093] 1. By comparing Example A1 with Example A2, it can be seen that Example A2 uses antique protective glazes on the market, while Example A1 uses antique protective glazes recorded in this scheme, which are composed of potassium feldspar, sodium feldspar, kaolin, zinc oxide, burned talc, wollastonite, barium carbonate and strontium carbonate. The surface stain resistance, skid resistance and Mohs hardness of Example A1 and Example A2 can meet the performance requirements. Among them, the skid resistance of Example A1 is R12, and the Mohs hardness is 8, which is better than Example A2 in terms of skid resistance and Mohs hardness. It shows that the use of antique protective glazes on the market in this scheme can meet the performance requirements of anti-slip corundum dry granule glaze, and the use of the raw materials of Example A1 can make the stain resistance, skid resistance and Mohs hardness have both, and maintain the best.
[0094] 2. By comparing Example A1 with Comparative Example A1, it can be seen that Comparative Example A1 does not add corundum powder to the anti-slip corundum dry granule glaze, and the matte dry granules and corundum powder will be arranged twice on the three-dimensional basic structure formed by the antique protective glaze during firing. Comparative Example A1 only has matte dry granules, and the particle size of the matte dry granules is 120-300 meshes; while the particle size of the corundum powder is 200-1200 meshes. On the one hand, the corundum powder of Comparative Example A1 is not formed into the finest particles arranged in the three-dimensional basic structure, and thus cannot form a basic undulating surface in the micrometer and millimeter range, so the anti-slip property of Comparative Example A1 is only R9. On the other hand, this scheme will also apply a hydrophobic and stain-resistant coating on the undulating surface in the subsequent process to form a hydrophobic and stain-resistant coating; and due to the lack of the basic undulating surface of the corundum powder part, the hydrophobic and stain-resistant coating cannot cross-link and solidify the three-dimensional structure of the corundum powder, and thus cannot form the final appearance of a hydrophobic and easy-to-clean surface, so the stain resistance is reduced and the Mohs hardness is reduced.
[0095] 3. By comparing Example A1 with Comparative Example A2, it can be seen that Comparative Example A2 does not add matte dry particles to the anti-slip corundum dry particle glaze, but uses ordinary dry particles instead of matte dry particles; the particle size of the matte dry particles in this solution is 120-300 mesh, and the initial melting temperature is greater than 1200°C; the initial melting temperature of the ordinary dry particles in Comparative Example A2 is 1100°C; the antique protective glaze selected in this solution can be fired in a kiln at a temperature greater than 1200°C, so it is necessary to ensure that the matte dry particles have an initial melting temperature greater than 1200°C; and the ordinary dry particles in Comparative Example A2 have melted before 1200°C, so before the basic layout is formed, the ordinary dry particles have begun to melt, thereby failing to form a dry particle structure on the formed three-dimensional basic structure. Therefore, in the basic layout of Comparative Example A2, there is only corundum powder, and no ordinary dry particles; because this solution requires the dry particles and corundum to cooperate with each other, the most important thing is that the basic surface morphology before firing can still be maintained after kiln firing, that is, the basic undulating surface with a roughness size in the range of microns and millimeters, and this undulating surface can lay the foundation for the subsequent anti-slip to reach R11 or above, and also prepare a good implantation for the subsequent preparation of the nano-hydrophobic layer. Comparative Example A2 does not have a three-dimensional structure of dry particles, so the surface stain resistance, stain resistance and Mohs hardness are reduced.
[0096] 4. By comparing Example A1 with Comparative Example A3, it can be seen that Comparative Example A3 does not add matte dry particles to the anti-slip corundum dry particle glaze, and the amount of corundum powder used is also relatively small. When entering the high temperature stage, the antique protective glaze has been completely melted and wrapped with the molten part of the corundum powder, so that a relatively rough dry particle surface structure cannot be formed on the formed three-dimensional basic structure. Therefore, after the comparative example A3 is discharged from the kiln, there is actually only a small amount of unmelted corundum powder on the basic layout, and there are no other dry particles, resulting in a decrease in the anti-slip function and Mohs hardness; because this scheme requires the dry particles and corundum to cooperate with each other, the most important thing is that the basic surface morphology before firing can still be maintained after the kiln is fired, that is, the basic undulating surface with a roughness size in the micrometer and millimeter range, and this undulating surface can lay the foundation for the subsequent anti-slip to reach R11 or above, and also prepare a good implantation for the subsequent preparation of the nano-hydrophobic layer.
[0097] Embodiment B:
[0098] The basic steps of Example B are the same as those of Example A1, with the only difference being that, in step (1), the hydrophobic and anti-fouling coating is applied to the blank by brushing.
[0099] The performance of Example A1 and Example B was tested, and the results are shown in Table 2 below.
[0100] Table 2 - Performance Tests of Example A1 and Example B
[0101] project Surface stain resistance Anti-slip Mohs hardness Example A1 qualified R12 Level 8 Example B qualified R10 Level 7
[0102] illustrate:
[0103] By comparing Example A1 with Example B, it can be seen that Example B does not use spraying to construct the hydrophobic and anti-fouling coating, but uses brushing to construct. The brushing method is carried out on a horizontal plane, and the film layer formed is relatively thick, and the more the protruding parts are brushed, the more unfavorable the anti-skid and Mohs hardness performance; while this scheme uses spraying as a construction method, and the hydrophobic and anti-fouling coating can be instantly filled into each gap of the base undulating surface in the micrometer and millimeter range by spraying, forming a complete film layer with a thickness of 1 to 5 microns; and the coating liquid flows under the action of its own weight, the deeper the depression, the thicker the film layer, and the corresponding anti-fouling and hydrophobic effects are more obvious, so that the tile has both anti-fouling, anti-skid and Mohs hardness. Example A1 is more stable than Example B in terms of the three-dimensional basic structure, so the anti-skid and Mohs hardness of Example A1 are better than Example B, which shows that using spraying as the construction method of the hydrophobic and anti-fouling coating of this scheme can improve the anti-skid and Mohs hardness.
[0104] Example C:
[0105] The basic steps of Example C are the same as those of Example A1, except that in step (3), the bricks are transferred to a dark environment for 6 hours.
[0106] The performance of Example A1 and Example C was tested, and the results are shown in Table 3 below.
[0107] Table 3 - Performance Tests of Example A1 and Example C
[0108] project Surface stain resistance Anti-slip Mohs hardness Example A1 qualified R12 Level 8 Example C qualified R11 Level 7
[0109] By comparing Example A1 with Example C, it can be seen that Example C does not perform step (3), while Step (3) of Example A1 uses epoxy acrylate resin as a curing agent, and the initial curing of the hydrophobic and stain-resistant coating is achieved by a silane coupling agent, and after the initial curing is completed, the epoxy acrylate resin can be photocured for 6 hours; in this way, Example A1 can produce further deep photocuring of the epoxy acrylate resin under the action of environmental ultraviolet rays such as sunlight, ensuring sufficient curing time without retaining a high temperature state, and the degree of curing of Example A1 is better, and the basic undulating ceramic three-dimensional structure is more stable. Therefore, Example A1 is better than Example C in terms of skid resistance and Mohs hardness, which shows that the use of epoxy acrylate resin for photocuring in the hydrophobic and stain-resistant coating can improve skid resistance and Mohs hardness.
[0110] Embodiment D:
[0111] A preparation process of a stain-resistant, non-slip and wear-resistant ceramic tile, comprising:
[0112] (1) Spray the anti-slip corundum dry granular glaze on the brick with the base glaze attached. The construction parameters are: specific gravity 1.4g / cm 3 , glaze spraying amount 200g / m2, nozzle aperture 0.6mm; fired in kiln at 1250℃; bottom glaze is purchased randomly on the market;
[0113] The anti-slip corundum dry particle glaze includes, by mass percentage: 40% antique protective glaze, 20% matte dry particles and 40% corundum powder, and an additional suspending agent is added in an amount 5 times the total mass of the corundum powder; the suspending agent is purchased randomly on the market.
[0114] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 1.5%; the particle size of the matte dry particles is 120-200 mesh, and the initial melting temperature is 1200°C; the particle size range of the corundum powder is 200-1100.
[0115] The antique protective glaze includes, by mass, 20 parts of potassium feldspar, 25 parts of sodium feldspar, 10 parts of kaolin, 8 parts of zinc oxide, 3 parts of burned talc, 5 parts of wollastonite, 15 parts of barium carbonate and 2 parts of strontium carbonate.
[0116] The chemical composition of matte dry granules, by mass percentage, includes: SiO 2 53%, Al 2 O 3 15%, K 2 O 10%, Na 2 O2.5%, CaO 6%, MgO 0.5%, BaO 1% and ZnO 12%.
[0117] (2) The bricks are taken out of the kiln, cooled to 250°C, and sprayed with a hydrophobic and stain-resistant coating, and the residual heat of the bricks is used to cure the hydrophobic and stain-resistant coating;
[0118] The hydrophobic and anti-fouling coating includes: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, silane coupling agent and epoxy acrylate resin; the size range of nano-silicon dioxide is 50nm;
[0119] The mass ratio of hydrogenated silicone oil: silicone resin: nano-silica: silane coupling agent: epoxy acrylate resin is 2.5:15:1:0.6:5.
[0120] (3) Transfer the bricks to an outdoor environment and continue to cure under sunlight for 6 hours.
[0121] Embodiment E:
[0122] A preparation process of a stain-resistant, non-slip and wear-resistant ceramic tile, comprising:
[0123] (1) Spray the anti-slip corundum dry granular glaze on the brick with the base glaze attached. The construction parameters are: specific gravity 1.2g / cm 3 , glaze spraying amount 100g / m2, nozzle aperture 0.72mm; fired in kiln at 1200℃; bottom glaze is purchased randomly on the market;
[0124] The anti-slip corundum dry particle glaze includes, by mass percentage: 50% antique protective glaze, 5% matte dry particles and 450% corundum powder, and an additional suspending agent is added in an amount that is 2 times the total mass of the corundum powder; the suspending agent is purchased randomly on the market.
[0125] The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2%; the particle size of the matte dry particles is 200-300 mesh, and the initial melting temperature is 1200°C; the particle size range of the corundum powder is 300-1000.
[0126] The antique protective glaze includes, by mass, 30 parts of potassium feldspar, 15 parts of sodium feldspar, 6 parts of kaolin, 2 parts of zinc oxide, 3 parts of burned talc, 5 parts of wollastonite, 25 parts of barium carbonate and 8 parts of strontium carbonate.
[0127] The chemical composition of matte dry granules, by mass percentage, includes: SiO 2 45%, Al 2 O 3 15%, K 2 O 10%, Na 2 O2%, CaO 15%, MgO 1%, BaO 2% and ZnO 10%.
[0128] (2) The bricks are taken out of the kiln, cooled to 250°C, and sprayed with a hydrophobic and stain-resistant coating, and the residual heat of the bricks is used to cure the hydrophobic and stain-resistant coating;
[0129] The hydrophobic and anti-fouling coating includes: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, silane coupling agent and epoxy acrylate resin; the size range of nano-silicon dioxide is 10nm;
[0130] The mass ratio of hydrogenated silicone oil: silicone resin: nano-silica: silane coupling agent: epoxy acrylate resin is 1:5:2:0.1:10.
[0131] (3) The bricks were transferred to an outdoor environment and continued to cure under sunlight for 7 hours.
[0132] The performance of Example D and Example E was tested, and the results are shown in Table 4 below.
[0133] Table 4 - Performance Tests of Example D and Example E
[0134] project Surface stain resistance Anti-slip Mohs hardness Example D qualified R12 Level 8 Example E qualified R12 Level 8
[0135] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze, characterized in that: In terms of percentage by mass, it comprises: 10-50% of antique protective glaze, 5-40% of matte dry particles and 10-50% of corundum powder, and an additional suspending agent of 1-5 times the total mass of the corundum powder; The antique protective glaze is ball-milled to a 325-mesh sieve residue of 0.2-1.5%, and the content of BaO plus MgO is greater than 20%; The matte dry particles have a particle size of 120 to 300 meshes and a melting point greater than 1200°C; The particle size of the corundum powder is 200-1200 meshes.
2. The anti-fouling, anti-skid, and wear-resistant anti-skid corundum dry granular glaze according to claim 1, characterized in that: The antique protective glaze comprises, by weight, 20 to 30 parts of potassium feldspar, 15 to 25 parts of sodium feldspar, 6 to 10 parts of kaolin, 2 to 8 parts of zinc oxide, 3 to 10 parts of calcined talc, 5 to 15 parts of wollastonite, 15 to 25 parts of barium carbonate and 2 to 8 parts of strontium carbonate.
3. The anti-fouling, anti-skid, and wear-resistant anti-skid corundum dry granular glaze according to claim 1 or 2, characterized in that: The chemical composition of the matte dry particles includes, by mass percentage, 45-65% of SiO2, 6-15% of Al2O3, 3-10% of K2O, 0-2.5% of Na2O, 6-15% of CaO, 0-1% of MgO, 0-2% of BaO and 3-12% of ZnO.
4. A glazing process for a dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze, using the dirt-resistant, skid-resistant, and wear-resistant anti-skid corundum dry granular glaze according to any one of claims 1 to 3, characterized in that: The anti-slip corundum dry granular glaze is applied by spraying; The construction parameters of the anti-slip corundum dry granular glaze are: specific gravity 1.2-1.6 g / cm 3 The glaze spraying amount is 100-250g / m2, and the nozzle aperture is 0.43-0.72mm.
5. A stain-resistant, non-slip and wear-resistant tile, characterized in that: include: body, wear-resistant and anti-skid layer and hydrophobic and anti-fouling coating; The wear-resistant and anti-skid layer is a dirt-resistant, anti-skid, wear-resistant and anti-skid corundum dry granular glaze as described in any one of claims 1 to 3; The wear-resistant and anti-skid layer is arranged on the surface of the blank; the hydrophobic and anti-fouling coating is applied on the surface of the wear-resistant and anti-skid layer; the hydrophobic and anti-fouling coating is prepared and cured by the hydrophobic and anti-fouling coating.
6. The stain-resistant, non-slip and wear-resistant ceramic tile according to claim 5, characterized in that: The hydrophobic and anti-fouling coating comprises: hydrogenated silicone oil, organic silicone resin, nano silicon dioxide, a silane coupling agent and a curing agent.
7. The stain-resistant, non-slip and wear-resistant ceramic tile according to claim 6, characterized in that: The size of the nano silicon dioxide is in the range of 10 to 50 nm.
8. A process for preparing stain-resistant, non-slip and wear-resistant tiles, characterized in that: The following steps are involved: (1) Using the anti-fouling, anti-skid, and wear-resistant anti-skid corundum dry granular glaze glazing process described in claim 4, the anti-skid corundum dry granular glaze is applied to the brick blank, and placed in a kiln for firing at 1200-1300° C.; (2) The bricks are taken out of the kiln, cooled to 100-250°C, and sprayed with a hydrophobic and anti-fouling coating, and the residual heat of the bricks is used to cure the hydrophobic and anti-fouling coating; The hydrophobic and anti-fouling coating includes: hydrogenated silicone oil, silicone resin, nano-silicon dioxide, silane coupling agent and curing agent.
9. The process for preparing a stain-resistant, non-slip and wear-resistant ceramic tile according to claim 8, characterized in that: Also includes: step (3); Step (3): transferring the bricks to an ultraviolet environment to continue curing; In the step (2), the curing agent includes: epoxy acrylate resin.
10. Use of an anti-slip corundum dry granular glaze in preparing stain-resistant, anti-slip and wear-resistant tiles, characterized in that: The anti-skid corundum dry granular glaze is a stain-resistant, anti-skid, and wear-resistant anti-skid corundum dry granular glaze as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Wear-resistant antiskid glaze and preparation method thereof as well as preparation method of wear-resistant antiskid tile
CN103570380A
Composite roller printing dry grain three-dimensional ceramic tile and production technology thereof
CN105565908A
Antifouling antiskid archaized brick and preparation method thereof
CN111153714A
Matt dry granular glaze, ceramic tile with matt dry granular glaze surface effect and preparation method of same
CN112174529A
Antifouling and antiskid archaized brick and preparation method thereof
CN114634376A
Cited By
Antifouling matte archaized brick with antiskid effect and preparation method of antifouling matte archaized brick
CN120157519A